Green approaches to heavy metal removal from wastewater: Microalgae solutions in a circular economy framework - Nikolaos A. Kazakis (Societal Impacts)
A new research project (ALGEBRA) has been launched, offering a green approach to heavy metal removal from wastewater, aligning with the principles of circular economy. The project involves the use of living cultures of microalgae, i.e., Chlorella vulgaris or Spirulina platensis, for the bioremediation of contaminated water bodies, while cultivating the microalgae at the same time. Experiments are conducted at both laboratory and large scales, under both controlled and real conditions, towards the investigation of the underlying mechanisms. Advanced instruments are used to determine the quantitative and qualitative properties of the produced biomass and the liquid medium. Efforts are also made to explore potential applications of the contaminated or regenerated cells. Machine learning techniques are also employed to analyze the acquired data and develop a model for the prediction of cell growth based on cultivation parameters, which will be validated in real case studies.